Kajian Penguasaan Konsep dan Keterampilan Proses Sains Pada Pelajaran Kimia Dengan Menggunakan Model Inkuiri Terbimbing - Rita Hartati (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
Need appropriate learning strategies so that students can more easily understand andimprove the control of chemical concepts, namely one using guided inquiry modelthrough the mastery of concepts and skills assessment process of science. Guided inquirylearning model where the students discover the concepts studied through experimentsin the implementation of the teacher providing guidance or instructions. The learningprocess of science using guided inquiry approach would involve the learners to be activeso that learning becomes more fun, not boring and achieve learning objective.